Determination of Phenolic Content, Ascorbic Acid, Antioxidant Activity and Antimicrobial Activity of Selected Fruit Waste - Nurfatihah Suhaimi, Syeril; Eileen Rizlan Ross, Erniee; Zubir, Ishak; Navaratnam, Shanti; Siva, Raseetha Siva (International Journal of Engineering and Technology, 2019)
The aim of this study was to determine the total phenolic content (TPC), antioxidant activity, ascorbic acid content and antimicrobial activity of extracts obtained from cocoa pod husk, banana peel and pineapple peel. Banana peel had significantly highest total phenolic content (154.50 mg GAE/g) followed by pineapple peel (140.37 mg GAE/g) and cocoa pod husk (114.08 mg GAE/g). Antioxidant activity of these samples measured using DPPH assays. Banana peel showed significantly higher DPPH scavenging activity (95.74%) compared to pineapple peel (84.96%) and cocoa pod husk (68.33%). Pineapple peel resulted in significantly higher (44.19 ppm) ascorbic acid as measured using High performance liquid chromatography (HPLC) method compared to banana peel (28.56 ppm). Cocoa pod husk, banana peel and pineapple peel were observed for antimicrobial activity against Escherichia coli, Staphylococcus aureus and penicillium. Samples extract at different concentrations in E. coli, S.aureus and penicillium-seeded Mueller-Hinton agar medium, resulted zone of inhibition after 24 h incubation in 37Â°C for bacteria and 72 h incubation in 28ÂºC. Banana peel at 20 and 25mg/ml against S.aureus resulted in zone of inhibition 9.67, 11.67 mm and cocoa pod husk with 8.00, 9.67 mm respectively. Cocoa pod husk at 15, 20 and 25mg/ml against E.coli resulted in zone of inhibition 7.33, 9.33 and 10.33 mm and banana peel with 6.67, 7.33 and 7.67 mm respectively. Pineapple peel does not showed any inhibition zone against tested bacteria and fungi.Â